Hubungan Persepsi dengan Dukungan Masyarakat pada Wanita Infertilitas - Romiko, Romiko; Kencana, Adelia Intan; Suzanna, Suzanna; Dekawaty, Ayu (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to determine the relationship between perceptions and community support for women with infertility. The research method uses quantitative descriptive analytical techniques with a cross-sectional approach. The research results show a relationship between perceptions and community support for women with infertility with a P value (0.000) < 0.05. In conclusion, the higher the public perception, the higher the public support. Keywords: Community support, infertility, perception